PENGARUH PROFESIONALISME AUDITOR DAN ETIKA PROFESI TERHADAP TINGKAT MATERIALITAS PENGAUDITAN LAPORAN KEUANGAN DAERAH - Rosdeana Theresia; Rahmiati Rahmiati; Yesika Yanuarisa (Balance: Media Informasi Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of auditor professionalism and profesional ethics on the materiality level of regional financial reports at the Inspectorate of Central Kalimantan Province. This research is a quantitative research, namely by presenting the results of the study in the form numbers which are then explained and interpreted in a description in order to test the hypothesis. The subjects in this study were internal auditors who worked at the Inspectorate of Central Kalimantan Province. The data used in this study are primary data obtained from respondents who filled out the questionnaire. The tools used in this research are descriptive statistics and multiple linear regression. Based on the results of the analysis, it is known that: 1) the professionalism of the auditors has a positive effect on the level of materiality in the auditing of regional financial statements in the province of Central Kalimantan, 2) professional ethics has a positive and significant effect on the level of materiality in the auditing of regional financial statements in the province of Central Kalimantan, 3) simultaneously the professionalism of auditors and professional ethics have a positive and significant effect on the level of materiality in the auditing of regional financial statements in Central Kalimantan Province.